Gold nanorod-based multiplex bioanalytical assay for the detection of CYFRA 21-1 and CA-125: towards oral cancer diagnostics. Issue 37 (16th September 2022) - Chakraborty, Debolina; Mukherjee, Amitava; Ethiraj, K. R.
Abstract : The study emphasizes the application of gold nanorods (GNRs) with different aspect ratios (ARs) for the development of multiplex assay for oral cancer detection. Abstract : The study emphasizes the application of gold nanorods (GNRs) with different aspect ratios (ARs) for the development of multiplex assay for oral cancer detection. The tunable optical properties of the GNRs that rely on the geometrical alterations of the nanostructure and the corresponding change in the refractive indices of the local environment form the basis of the label-free biosensing mechanism. In the present work, two GNRs with AR 2.1 and AR 3.9 exhibiting LSPR at 620 and 775 nm were used for sensing oral cancer biomarkers (Cyfra 21-1 and CA-125). Clinically relevant salivary concentrations of CYFRA 21-1 and CA-125 were taken into consideration for designing the assay range. Herein, the antibodies against Cyfra 21-1 and CA-125 have been employed as biospecific probes to functionalize the GNRs with different ARs. Molecular interactions that induce a spectral shift of distinct plasmon band maxima facilitated quantitative assessment of the target analyte. The GNR bioprobe employed for sensing Cyfra 21-1 had a wide linear detection range of 0.496–48.4 ng mL −1 with a detection limit as low as 0.84 ng mL −1 and for CA-125 the detection range was 5–320 U mL −1 with a detection limit of 1.6 U mL −1 . The individual GNR bioprobe also showed high specificity against several interferents. For multiplexed biosensing, the plasmon spectra of the GNR bioprobe mixture showed distinct responses upon binding of single and dual targets in the sample mixture and/or artificial saliva. The quantitative data from the developed method are of high clinical significance that can aid in the understanding of clinicopathological advancements in oral cancer at an early stage. This simple yet novel nanosized optical transducer technology can be further converted into miniaturized biochips and can be deployed in clinics as a nanoparticle-based point-of-care diagnostic adjunct.